Temporary Internal Migration: Inferences from Survey Data - Edwards, Wayne (Journal of Northern Studies, 2014)
It is well established in the literature that an important reason why people move from place to place is to seek employment. One way to balance non-job considerations against the need for a wage income is to move to another place temporarily for a job opportunity. By making a temporary move, an individual can maintain his or her residence in a community, thereby retaining place level amenities, family relationships, traditional activities, and so on. Temporary migration for market work might be an especially attractive solution for people who have strong community ties but few job opportunities. This paper concentrates on the case of internal temporary migration for job market reasons in Alaska. Some U.S. Census data are useful for analysis of migration, but those data are not collected frequently enough to address temporary migration questions well. Using a set of pre-existing non-Census surveys, this paper examines temporary migrants in north and northwest Alaska. For the investigated area, approximately 8 per cent to 16 per cent of the population are engaged in temporary migration for market work. Substantial seasonal differences in temporary migration rates are uncovered, as are gender differences.